1999
DOI: 10.1557/s1092578300000703
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation in GaN layers grown on porous GaN sublayers

Abstract: We have studied epitaxial GaN layers grown by hydride vapour phase epitaxy (HVPE) on porous GaN sublayers formed on SiC substrates. It was shown that these layers can be grown with good surface morphology and high crystalline quality. X-ray, Raman and photoluminescent (PL) measurements showed that the stress in the layers grown on porous GaN was reduced to 0.1-0.2 GPa, while the stress in the layers grown directly on 6H-SiC substrates remains at its usual level of about 1 GPa. Thus, we have shown that growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 10 publications
1
28
0
1
Order By: Relevance
“…Cracks formed in GaN layers grown on both porous and nonporous SiC substrates. Thus the porous SiC substrate did not act as a compliant substrate (thereby absorbing the tensile thermal stress elastically) as has been suggested previously [2,3]. This fact is consistent with the arguments of Kästner et al that a porous substrate cannot act as a compliant substrate for a film with large (~1 cm) lateral dimension [11].…”
Section: Figures 4(a) and (B)supporting
confidence: 90%
See 2 more Smart Citations
“…Cracks formed in GaN layers grown on both porous and nonporous SiC substrates. Thus the porous SiC substrate did not act as a compliant substrate (thereby absorbing the tensile thermal stress elastically) as has been suggested previously [2,3]. This fact is consistent with the arguments of Kästner et al that a porous substrate cannot act as a compliant substrate for a film with large (~1 cm) lateral dimension [11].…”
Section: Figures 4(a) and (B)supporting
confidence: 90%
“…Porous SiC has attracted considerable interest in the recent years as an attractive substrate for epitaxy of GaN and SiC [1][2][3][4][5][6]. Earlier studies have shown improved GaN film quality on porous SiC [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous SiC and GaN has recently been explored as promising substrates to grow epitaxial SiC or GaN with reduced dislocation density [1][2][3][4][5][6]. Such porous materials are produced by anodizing n-type SiC in hydrofluoric acid (HF) under ultra-violet illumination [7].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results for GaN growth on porous GaN have shown some promise for improved GaN quality [2][3][4]. It has been speculated that a porous surface may serve as a template for nano-scale lateral epitaxial overgrowth [4], and that a porous substrate layer may be compliant to any lattice and thermal mismatch strains [2][3][4]. In this work we grew GaN films on both porous and non-porous SiC substrate under nominally identical conditions and evaluated the effect of using the porous substrate.…”
Section: Introductionmentioning
confidence: 99%